A systematic review on the impact of social support on college students' wellbeing and mental health. - Li Ruihua; Norlizah Che Hassan; Zhu Qiuxia; Ouyang Sha; Dong Jingyi (PLoS ONE, 2025)
In recent years, growing attention has been directed toward undergraduate students' mental health and overall well-being. The transition to university life, coupled with academic and social demands, has been shown to strain students' psychological functioning considerably. Social support is often cited as a protective factor that can help mitigate these pressures; however, in-depth investigations focusing specifically on this relationship within the college student demographic remain relatively limited. This review examines how social support influences university students' mental health and well-being outcomes. A systematic analysis was carried out, encompassing 51 empirical studies published between 2010 and 2024. These studies were identified through a comprehensive search of six major academic databases: Web of Science (WOS), Scopus, ProQuest, APA PsycINFO, PubMed, and Cochrane. The review highlights the nuanced relationship between social support and student well-being, underscoring the significance of social resources in shaping psychological outcomes during the higher education experience. The review identified both direct and indirect effects of social support. Direct effects include improved psychological and emotional well-being, reduced stress, and better health behaviours. Indirect effects highlight social support's role as a mediator, enhancing resilience, self-esteem, and life satisfaction by providing emotional and informational resources. These results emphasize the importance of nurturing supportive relationships to promote student well-being.